A proteasome-resistant fragment of NIK mediates oncogenic NF-κB signaling in schwannomas. (17th October 2018) - Gehlhausen, Jeffrey R; Hawley, Eric; Wahle, Benjamin Mark; He, Yongzheng; Edwards, Donna; Rhodes, Steven D; Lajiness, Jacquelyn D; Staser, Karl; Chen, Shi; Yang, Xianlin; Yuan, Jin; Li, Xiaohong; et al.
Abstract: Schwannomas are common, highly morbid and medically untreatable tumors that can arise in patients with germ line as well as somatic mutations in neurofibromatosis type 2 ( NF2 ). These mutations most commonly result in the loss of function of the NF2 -encoded protein, Merlin. Little is known about how Merlin functions endogenously as a tumor suppressor and how its loss leads to oncogenic transformation in Schwann cells (SCs). Here, we identify nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κ B)-inducing kinase (NIK) as a potential drug target driving NF-κ B signaling and Merlin-deficient schwannoma genesis. Using a genomic approach to profile aberrant tumor signaling pathways, we describe multiple upregulated NF-κ B signaling elements in human and murine schwannomas, leading us to identify a caspase-cleaved, proteasome-resistant NIK kinase domain fragment that amplifies pathogenic NF-κ B signaling. Lentiviral-mediated transduction of this NIK fragment into normal SCs promotes proliferation, survival, and adhesion while inducing schwannoma formation in a novel in vivo orthotopic transplant model. Furthermore, we describe an NF-κ B-potentiated hepatocyte growth factor (HGF) to MET proto-oncogene receptor tyrosine kinase (c-Met) autocrine feed-forward loop promoting SC proliferation. These innovative studies identify a novel signaling axis underlying schwannoma formation, revealing new and potentially druggable schwannoma vulnerabilities with future therapeutic potential.